2009 13th International Conference Information Visualisation 2009
DOI: 10.1109/iv.2009.100
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Visual Analysis of Lexical Networks

Abstract: A lexical network is a very useful resource for natural language processing systems. However, building high quality lexical networks is a complex task. "Jeux de mots" is a web game which aims at building a lexical network for the French language. At the time of this paper's writing, "jeux de mots" contains 164 480 lexical terms and 397 362 associations. Both lexical terms and associations are weighted with a metric that determines the importance of a given term or association. Associations between lexical term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The above work shows the feasibility of crowdsourcing VerbNet semantic entailments, as has been shown for a handful of other linguistic judgments (Artignan, Hascoet and Lafourcade, 2009;Poesio et al, 2012;Venhuizen et al, 2013). There are many domains in which gold standard human judgments are scarce; crowd-sourcing has considerable potential at addressing this need.…”
Section: Discussionsupporting
confidence: 71%
“…The above work shows the feasibility of crowdsourcing VerbNet semantic entailments, as has been shown for a handful of other linguistic judgments (Artignan, Hascoet and Lafourcade, 2009;Poesio et al, 2012;Venhuizen et al, 2013). There are many domains in which gold standard human judgments are scarce; crowd-sourcing has considerable potential at addressing this need.…”
Section: Discussionsupporting
confidence: 71%
“…There have been many studies involving gamification for annotation tasks including anaphora resolution (Hladká et al, 2009;Poesio et al, 2013), paraphrasing (Chklovski and Gil, 2005), term associations (Artignan et al, 2009), and disambiguation (Seemakurty et al, 2010;Venhuizen et al, 2013). Recent studies (Vannella et al, 2014; showed that designing linguistic annotation tasks as video games can produce high-quality annotations compared to textbased tasks.…”
Section: Related Workmentioning
confidence: 99%
“…Multiple works have proposed linguistic annotation-based games with a purpose for tasks such as anaphora resolution (Hladká et al, 2009;Poesio et al, 2013), paraphrasing (Chklovski and Gil, 2005), term associations (Artignan et al, 2009;Lafourcade and Joubert, 2010), query expansion (Simko et al, 2011), and word sense disambiguation (Chklovski and Mihalcea, 2002;Seemakurty et al, 2010;Venhuizen et al, 2013). Notably, all of these linguistic games focus on users interacting with text, in contrast to other highly successful games with a purpose in other domains, such as Foldit (Cooper et al, 2010), in which players fold protein sequences, and the ESP game (von Ahn and Dabbish, 2004), where players label images with words.…”
Section: Related Workmentioning
confidence: 99%